2015
DOI: 10.1590/0102-33062015abb0112
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of low light and water stress on Jatropha curcas L. promotes shoot growth and morphological adjustment

Abstract: Jatropha curcas (physic nut) is a plant with economic and pharmaceutical uses. Basic studies on the influence of environmental factors on the early development of J. curcas are important for improving farming techniques and increasing productivity. This study investigated the adjustments of J. curcas to the environmental factors of drought and light stress in order to determine which factors most strongly affect the allocation of biomass during early growth. Leaves, stems, and roots of young plants were sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…Thinner leaves are more able to use low light efficiently by promoting SLA and decreasing SLW to maximize more carbon gain [28]. Other studies also find an increment in LA and SLA under low light stress [33,34], thus confirming the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Thinner leaves are more able to use low light efficiently by promoting SLA and decreasing SLW to maximize more carbon gain [28]. Other studies also find an increment in LA and SLA under low light stress [33,34], thus confirming the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…In turn, shading improved Ψw even at the highest water deficit stress, which increased to -1.72 MPa and -1.93 MPa in Om Rabiaa and Maali cultivars, respectively. Carneiro et al, (2015) put forth the idea that the improved performance of shaded plants may also be related to better conditions both in terms of temperature and humidity. In addition, we showed a variation for drought tolerance between the two cultivars.…”
Section: Resultsmentioning
confidence: 99%
“…Drought and light are not independent either in space or in time and may cause a variety of plant responses which can be additive, synergistic or antagonistic. In semiarid and arid environments, shading with lower levels of water deficit and cooler temperatures may be an intermediate solution for reducing plant water stress (Nicolas et al, 2008), but it can also aggravate the growth of seedlings exposed to drought (Carneiro et al, 2015). Since water availability and light are often the main factors affecting productivity in dry regions, strategies to improve sustainable use of water and plant drought tolerance are of paramount interest (Dolferus, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some limited literature available (mostly on woody seedlings) regarding the effect of co-occurring shade and drought stress on plant growth is elicited below. Carneiro et al (2015) found that when shade (70%) grown Jatropha curcas plants were subjected to long-term water deficit conditions (irrigation withheld until signs of stress, i.e., leaf tipping and wilting became evident), the biomass allocated to roots was lowered by > 40% though the root length did not change. However, the leaf size of plants grown in co-occurring shade and drought stress was considerably greater than those grown under full sun and drought environment.…”
Section: Plant Responses To Co-occurring Shade and Drought Stressmentioning
confidence: 99%